2022
DOI: 10.3389/fbioe.2022.913423
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Knee Joint Angle and Contraction Intensity on the Triceps Surae Stiffness

Abstract: Purpose: Monitoring the contractility of muscles assists the clinician in understanding how muscle functions as part of the kinetic system. This study investigated the effect of knee joint angles under different resistance on the stiffness of the medial gastrocnemius (MG), lateral gastrocnemius (LG), and soleus (SOL) muscles using the shear wave elastography (SWE) technique.Methods: A total of 22 females were recruited. During isometric plantar flexion, at knee 0-degree (fully extended) and knee 90-degree (fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Our recent research has shown that joint exion angle and rotation, as independent factors or interactive effects, can have a signi cant impact on corresponding muscle hardness and muscle strength 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Our recent research has shown that joint exion angle and rotation, as independent factors or interactive effects, can have a signi cant impact on corresponding muscle hardness and muscle strength 34 .…”
Section: Discussionmentioning
confidence: 99%
“…It transmits and tracks shear waves to obtain Shear modulus values, and dynamically depicts the distribution of SWE in target tissues in real time ( Niu et al, 2022 ). Shear modulus value can be used to quantify local muscle stiffness ( Chalchat et al, 2022 ), and tiffness is a proxy for the force of muscle contraction ( Lin et al, 2022 ). Evaluating the passive and active mechanical properties of QF can reflect the contractile performance of its muscles.…”
Section: Introductionmentioning
confidence: 99%